Bridging the gap between the sciences and the humanities in nigeria: literature and the wale okediran example (2022)
The dichotomy between the sciences and the humanities has continued to be a concern, particularly in the 21st Century. However, conscious and consistent efforts are being made globally at bridging the gap through the promotion of interaction and multidisciplinary approach to issues. Contemporary studies on these have not only engaged from diverse theoretical positions but have made specific interventions in reconstructing the link that will synergise both in the new world order. This study juxtaposes these realities vis -a-vis the purpose and significance of the sciences and the humanities as separate enterprises, and when melded together as a single enterprise. Taking bearing from the medical practices of Sigmund Freud, his interpretations and diagnostic approach to literature; this paper examines the professional experience of Wale Okediran and his literary writings. Okediran, a Nigerian physician, writer and politician, through his work, social and political interaction further ennobles the fusion of the sciences and the humanities in being able to conscientise and positively influence his society.